Profiling of Sensory Attributes the Fish Bonggolan from Gresik Using the RATA (Rate-All-That-Apply) Method - Muhammad Bagus Amrulloh; Sri Winarti; Andre Yusuf Trisna Putra (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Fish bonggolan is a traditional fish-based snack from Sidayu District, Gresik Regency, produced by local micro, small, and medium enterprises (MSMEs). Variations in raw material composition and processing methods among producers lead to differences in sensory characteristics and consumer acceptance. This study aimed to identify the sensory attribute profiles of fish bonggolan from six different MSMEs in Sidayu District using the Rate-All-That-Apply (RATA) method and to determine sensory attributes influencing consumer preferences. Sensory attributes were identified through a Focus Group Discussion (FGD) involving 10 semi-trained panellists, yielding 17 attributes grouped into aroma, colour, taste, and texture parameters. Sensory evaluation was conducted by untrained panelists using the RATA method combined with a hedonic test. The data were analyzed using the Kruskal–Wallis test followed by Dunn’s post hoc test, Principal Component Analysis (PCA), and preference mapping. The results showed significant differences (p < 0.05) in most sensory attributes among samples, except for leafy aroma and umami taste. PCA revealed distinct sensory profiles for each sample. Preference mapping indicated that sample P2 achieved the highest consumer liking score (80–100%), while sample P6 showed the lowest liking score (20–40%). These findings demonstrate that specific sensory attributes strongly influence consumer acceptance and may serve as a basis for product improvement and market standardization of fish bonggolan. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 8: Decent Work and Economic GrowthSDG 12 : Responsible Consumption and Production